Kecenderungan Kepemimpinan Kyai Pengasuh Pondok Pesantren Darun Najah Tegalsari Semen Kediri - Nur Hidayat (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
The existence of a kyai in peasantries takes possession of the central position. Leadership Kyai often with the attribute of leadership charismatic. Kyai with its leadership is strong can move forward the peasantries better, on the contrary kyai with weak leadership make the peasantries remain stagnant even little by little identity from marionette peasantries will sink and belief from society. Model the leadership applied very determining its member involvement intensity in organizational activity plan. But that way, a factor of leadership style still represents the determinant of effectiveness and activity efficiency of an organization. This research use the descriptive research approach qualitative, in the form of utterance or article and behavior perceived the. Research type used by case study. The conclusion from this research result is a style of leadership kyai in Maisonette of Pesantren Darun Najah Tegalsari Cement the Kediri is inclusive of into democratic leadership taking root at charismatic.